19 Do patients with COVID-19 require different end of life medications? – The experiences of a dual site Hospital Palliative Care Team. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Boulstridge, Lisa; Wall, Jillian; England, Ruth; Curtis, Hannah
Abstract : Introduction: University Hospitals of Derby and Burton (UHDB) report our Hospital Palliative Care Team's (HPCT) experience in supporting patients with COVID-19 during the pandemic's first surge. Methods: Inclusion criteria: patients supported by HPCT at two acute hospital sites, with a positive RT-PCR nasopharyngeal swab for SARS-CoV-2 between 16th March and 1st May 2020. Exclusion criteria: Patients intubated on ITU. Data was extracted from medical and nursing notes retrospectively and prescriptions in the last 3 days of life were reviewed. We sought to describe the cohort of COVID-19 patients supported by HPCT and to evaluate their medication requirements at end of life. Results: 223 patients were referred to HPCT: 155 (70%) with a positive swab for SARS-CoV-2. 95% had never been seen by HPCT previously. On average they had had one hospital admission in the preceding 12 months (range 1–8). The proportion of non-white patients was higher than our usual cohort (7 vs 4.6%). Whilst receiving input from HPCT 112 (72%) patients died in hospital and only 4% were discharged from hospital. All patients had anticipatory medications prescribed during their last 3 days of life; 41% required at least one dose in the 2 days before death, and 62% on the day of death. On the day of death, 59% required a dose of an opiate, 60% midazolam and 20% an antipsychotic; 72% had a syringe driver in place. However 23% required no anticipatory medications or a syringe driver. Doses of drugs given did not exceed those typically used in non-COVID patients. Conclusions: The vast majority of patients during this period of time were new referrals to HPCT. In line with other published work, most patients dying with COVID-19 had symptoms which were managed with usual doses of medications. An opiate and midazolam were the drugs most frequently required.